การเตรียมและสมบัติของพอลิโพรพิลีน/เอทิลีนออกทีนโคพอลิเมอร์/โวลลาสโทไนต์คอมพอสิต - หฤทศัย ไวปัญญา (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
In this study, ethylene octene copolymer (EOC) with 24 wt% octene and wollastonite with particle size of 1200 mesh were employed to prepare polypropylene (PP)/EOC/wollastonite composites. PP was melt mixed with various loadings of EOC (20 and 30 wt %) and wollastonite (10, 20 and 30 parts per hundred resin) using twin screw extruder. The extrudates were pelletized and then injection molded into test specimens. The effects of EOC and wollastonite on the tensile properties, flexural strength, impact strength, dynamic mechanical properties, flammability and thermal properties were investigated. Deterioration in tensile and flexural strength, Young’s modulus, flexural modulus and storage modulus with the inclusion of elastomeric EOC has been observed. However, these properties were improved with the addition of wollastonite. It is also found that the elongation at break, impact strength and char formation were increased in all of the compositions as compared to the neat PP. DSC and DMA analysis revealed a decrease in the degree of crystallinity and glass transition temperature, respectively with the incorporation of EOC and wollastonite. Moreover, the values of the onset and 50% degradation temperatures obtained from TGA thermograms and limiting oxygen index were not improved by either EOC or wollastonite.